Developing a mechanism of construction project manager’s emotional intelligence on project success: A grounded theory research based in China - Zhang, Qi; Hao, Shengyue (Frontiers in Psychology, 2022)
A project manager’s emotional intelligence (EI) is essential to project success. However, the mechanism in this cause and effect remains a black box in extant literature. China is now the world’s largest construction market, and figuring out the mechanism of construction project manager’s (CPM’s) EI on project success is meaningful for developing the global construction market. This study conducted an in-depth interview with 24 CPMs with more than five-year experience in construction project management. The grounded theory was employed to profile the application of CPM’s EI and to build the multi-level mechanism that explains the influence of CPM’s EI on project success. The mechanism framework conforms to the existed IPO (Input-Process-Output) theory. It consists of a team-level mechanism (including the positive team atmosphere, shared vision, and team cohesion) and an individual-level mechanism (i.e., organizational citizenship behavior directed at the organization, perceived supervisor support, trust in leader and subordinate’s psychological and emotional health). This study further proposed that the effect of this mechanism does not work immediately but develops with time passing. Implications for further research and project management practice are discussed in the end.